Asymmetric epoxidation of α, β-unsaturated aldehydes catalyzed by a spiro-pyrrolidine-derived organocatalyst. Issue 6 (1st April 2016) - Xu, Ming-Hui; Tu, Yong-Qiang; Tian, Jin-Miao; Zhang, Fu-Min; Wang, Shao-Hua; Zhang, Shi-Heng; Zhang, Xiao-Ming
Graphical abstract: Abstract: The asymmetric epoxidation of α, β-unsaturated aldehydes, catalyzed by a spiro-pyrrolidine (SPD)-derived organocatalyst, has been accomplished with good diastereoselectivities (up to dr >20:1) and with high to excellent enantioselectivities (up to 99% ee). Abstract : (((2 S, 3 S )-3-Phenyloxiran-2-yl)methanol: C9 H10 O2 [ α ]D 20 = −47 ( c 1.0, CHCl3 ) Source of chirality: the organocatalyst Absolute configuration: (2 S, 3 S ) Abstract : ((2 S, 3 S )-3-(4-Bromophenyl)oxiran-2-yl)methanol: C9 H9 BrO2 [ α ]D 20 = −32.0 ( c 0.41, CHCl3 ) Source of chirality: the organocatalyst Absolute configuration: (2 S, 3 S ) Abstract : ((2 S, 3 S )-3-(4-Chlorophenyl) oxiran-2-yl)methanol: C9 H9 ClO2 [ α ]D 20 = −38 ( c 1.0, CHCl3 ) Source of chirality: the organocatalyst Absolute configuration: (2 S, 3 S ) Abstract : ((2 S, 3 S )-3-(2-Fluorophenyl)oxiran-2-yl)methanol: C9 H9 FO2 [ α ]D 20 = −23 ( c 1.0, CHCl3 ) Source of chirality: the organocatalyst Absolute configuration: (2 S, 3 S ) Abstract : ((2 S, 3 S )-3-(3-fluorophenyl)oxiran-2-yl)methanol: C9 H9 FO2 [ α ]D 20 = −44 ( c 1.0, CHCl3 ) Source of chirality: the organocatalyst Absolute configuration: (2 S, 3 S ) Abstract : ((2 S, 3 S )-3-(4-Fluorophenyl)oxiran-2-yl)methanol: C9 H9 FO2 [ α ]D 20 = −35 ( c 1.0, CHCl3 ) Source of chirality: the organocatalyst Absolute configuration: (2 S, 3 S ) Abstract : ((2 S, 3 S )-3-( p -Tolyl) oxiran-2-yl)methanol: C10 H12 O2 [ α ]D 20 = −36 ( c 1.0, CHCl3 ) Source of chirality: the organocatalyst Absolute configuration: (2 S, 3 S ) Abstract : ((2 S, 3 S )-3-(Naphthalen-1-yl) oxiran-2-yl)methanol: C13 H12 O2 [ α ]D 20 = −66 ( c 1.0, CHCl3 ) Source of chirality: the organocatalyst Absolute configuration: (2 S, 3 S ) Abstract : ((2 S, 3 S )-3-Methyloxiran-2-yl) methyl 4-nitrobenzoate: C11 H11 NO5 [ α ]D 20 = −14 ( c 1.0, CHCl3 ) Source of chirality: the organocatalyst Absolute configuration: (2 S, 3 S ) Abstract : ((2 S, 3 S )-3-Ethyloxiran-2-yl) methyl-4-nitrobenzoate: C12 H13 NO5 [ α ]D 20 = −23 ( c 1.0, CHCl3 ) Source of chirality: the organocatalyst Absolute configuration: (2 S, 3 S ) Abstract : ((2 S, 3 S )-3-Propyloxiran-2-yl) methyl-4-nitrobenzoate: C13 H15 NO5 [ α ]D 20 = −32 ( c 1.0, CHCl3 ) Source of chirality: the organocatalyst Absolute configuration: (2 S, 3 S ) Abstract : ( S )-(3, 3-dimethyloxiran-2-yl) methyl-4-nitrobenzoate: C12 H13 NO5 [ α ]D 20 = −22 ( c 1.0, CHCl3 ) Source of chirality: the organocatalyst Absolute configuration: (1 S ) Abstract : ( S )-1-Oxaspiro [2.4] heptan-2-ylmethyl-4-nitrobenzoate: C14 H15 NO5 [ α ]D 20 = −17 ( c 1.0, CHCl3 ) Source of chirality: the organocatalyst Absolute configuration: (1 S ) Abstract : ((2 S, 3 R )-3-Heptyl-3-methyloxiran-2-yl)methyl 4-nitrobenzoate: C18 H25 NO5 [ α ]D 20 = −11 ( c 1.0, CHCl3 ) Source of chirality: the organocatalyst Absolute configuration: (2 S, 3 R ) Abstract : (5 R, 6 R )-6-(( tert -Butyldiphenylsilyl)oxy)-1-azaspiro[4.4]nonane: C24 H33 NOSi [ α ]D 20 = −22 ( c 1.0, CHCl3 ) Source of chirality: the organocatalyst Absolute configuration: (5 R, 6 R )